The effect of mesenchymal stem cells' secretome on lung cancer progression is contingent on their origin: primary or metastatic niche. (December 2018) - Attar-Schneider, Oshrat; Drucker, Liat; Gottfried, Maya
Abstract The fatality of non-small-cell lung cancer (NSCLC) and the role of the cancer microenvironment in its resistance to therapy are long recognized. Accumulating data allocate a significant role for mesenchymal stem cells (MSCs) in the malignant environment. Previously, we have demonstrated that MSCs from NSCLC metastatic bone marrow (BM) niche deleteriously affected NSCLC cells. Here, we have decided to examine the effect of MSCs from the primary niche of the lung (healthy or adjacent to tumor) on NSCLC phenotype. We cultured NSCLC cell lines with healthy/NSCLC lung-MSCs conditioned media (secretome) and showed elevation in cells' MAPKs and translation initiation signals, proliferation, viability, death, and migration. We also established enhanced autophagy and epithelial to mesenchymal transition processes. Moreover, we observed that MSCs from tumor adjacent sites (pathological niche) exhibited a more profound effect than MSCs from healthy lung tissue. Our findings underscore the capacity of the lung-MSCs to modulate NSCLC phenotype. Interestingly, both tumor adjacent (pathological) and distant lung-MSCs (healthy) promoted the NSCLC's TI, proliferation, migration, and epithelial to mesenchymal transition, yet the pathological MSCs displayed a greater affect. In conclusion, by comparing the effects of normal lung-MSCs, NSCLC adjacent MSCs, and BM-MSCs, we have established that the primary and metastatic niches display opposite and critical effects that promote the cancerous systemic state. Specifically, the primary site MSCs promote the expansion of the malignant clone and its dispersion, whereas the metastatic site MSCs facilitates the cells re-seeding. We suggest that sabotaging the cross-talk between MSCs and NSCLC affords effective means to inhibit lung cancer progression and will require different targeting strategies in accordance with niche/disease stage. This study demonstrates that lung mesenchymal stem cells promote non-small cell lung cancer proliferation and migration in a MAPK/translation initiation/autophagy-dependent manner. The authors describe how primary and metastatic niches display opposite and critical effects, both crucial to cancer progression.